Theological Significance of the Marian Title “Morning Star” - Wojtczak, Adam (Studia Warmińskie, 2011)
The article presents theological meaning of the Marian title “Morning Star”. The article consists of three paragraphs. The first one portrays Mary as the Morning Star that preceded, prepared and heralded the historical coming of the Messiah–Sun. She handed the Light of God to humanity and opened up a new era in history. The second paragraph discusses Mary’s participation in the life and salvific mission of the Son. Before he began talking about himself and his mission, it was her who talked about him. During his public activity, she receded into the background, in order for a new family to grow. Being his Teacher, she later became a Disciple of her Son. The third paragraph introduces the presence of Mary – the Leading Star upon the path of faith of the Church. After the Ascension of Christ, she is found at the Cenacle among his disciples so as to prepare the descent of the Holy Spirit and the birth of the Church. Since then she has been leading the Church towards the ultimate goal. She does so in a twofold way. For the pilgrims, she is a model of faith, hope and love. She is also the spiritual Mother of all humanity. They plead with her for her motherly intercession upon the path of faith. All in all, it turns out that Mary-Morning Star is a reflection of Christ and she praises him, not herself.